2011
DOI: 10.1016/j.jchromb.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical probes for analysis of carbonylated proteins: A review

Abstract: Protein carbonylation is a major form of protein oxidation and is widely used as an indicator of oxidative stress. Carbonyl groups do not have distinguishing UV or visible, spectrophotometric absorbance/fluorescence characteristics and thus their detection and quantification can only be achieved using specific chemical probes. In this paper, we review the advantages and disadvantages of several chemical probes that have been and are still being used for protein carbonyl analysis. These probes include 2, 4-dini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 91 publications
(115 reference statements)
0
74
0
Order By: Relevance
“…A chromophore that reacts with a broader range of aldehydes is 1,3-cyclohexanedione (CHD) [85,86], although it has declined in popularity in favor of other reagents. 2,4-dinitrophenylhydrazine (DNPH) is a very commonly used probe that reacts to give a dinitrophenylhydrazone product with an absorbance at 380 nm [87]; it can be used to quantify free aldehydes, although it is also often used to detect carbonyls on proteins by ELISA or western blotting, as described below. Recently, a number of new methods and probes have been developed as improved methods to measure free lipid peroxidation derived aldehydes, and applied to the analysis of human plasma, serum or urine samples, as detailed in Table 2.…”
Section: Analysis Of Free Aldehydic Oxidation Products and Their Metamentioning
confidence: 99%
“…A chromophore that reacts with a broader range of aldehydes is 1,3-cyclohexanedione (CHD) [85,86], although it has declined in popularity in favor of other reagents. 2,4-dinitrophenylhydrazine (DNPH) is a very commonly used probe that reacts to give a dinitrophenylhydrazone product with an absorbance at 380 nm [87]; it can be used to quantify free aldehydes, although it is also often used to detect carbonyls on proteins by ELISA or western blotting, as described below. Recently, a number of new methods and probes have been developed as improved methods to measure free lipid peroxidation derived aldehydes, and applied to the analysis of human plasma, serum or urine samples, as detailed in Table 2.…”
Section: Analysis Of Free Aldehydic Oxidation Products and Their Metamentioning
confidence: 99%
“…Several different chemical probes for detection of protein carbonyls have been developed including DNPH, tritiated sodium borohydride, biotin hydrazine-containing probes and fluorescent probes. Properties of these probes have been reviewed recently [43]. The most widely used system for detecting carbonylated proteins on 2D gels is based on DNPH derivatisation and immunodetection with anti-DNPH antibody.…”
Section: D Gel Based Proteomicsmentioning
confidence: 99%
“…One of the most common types of oxidative modification is protein carbonylation, the introduction of carbonyl groups (CÂźO) in a protein [12]. We chose protein carbonylation as a marker of oxidative stress, because it is a reliable indicator of oxidative damages [13], suitable for proteomic analysis [14] and commonly used on mdx muscle [15,16]. Studies reported an abnormal oxidative stress in skeletal muscle of DMD patients and mdx mice [17,18].…”
Section: Introductionmentioning
confidence: 99%